Holistic wetland restoration: Can participatory approaches help to reach it? - Victor Francisco Pajuelo Madrigal 1987- (2017)
Wetlands are sites of complex interactions between humans and non-humans that have been usually treated as linear and simple systems. Awareness of their complexity and ecological importance has led to increased emphasis on their protection and restoration in a holistic way. Such holistic approaches usually claim the need to incorporate all the humans and non-humans involved. Thus, from a complexity theory perspective, participation and involvement has been advocated as the most adequate method to reach holistic approaches within ecological restoration. However, this study claims that any holistic restoration based on participation must operate with a certain structure to be successful. Certain ontologies, communities and spaces for dialogue must be present for participation to lead to a holistic outcome. With the help of object-oriented ontology and Latour’s political ecology, a theoretical framework for participation is outlined, based on a non-dualistic ontology and the concept of place which, it is argued, enables the space needed for dialogue. This framework is explored through a case study of a wetland disturbance and restoration at Bjarnarfjörður (Strandir, Iceland), where the current Icelandic wetland restoration policy is explored and contrasted with a participatory approach to restoration. Semi-structured interviews, group meetings and a participatory GIS process were used to highlight the shortcomings of the current approach and explore the possibilities for participation at wetland restoration sites in a holistic manner. This study claims that, under the current approach, participation is not able to lead to holistic outcomes. Even though, the process of participation is still defended, as it shapes those communities towards a future allowance of holistic restoration. Votlendi eru svæði þar sem fjölþætt samspil mennskra og ómennskra aðila á sér stað. Oftast hafa þau verið meðhöndluð sem línuleg, einföld kerfi. Meiri vitneskja um hversu flókin og vistfræðilega mikilvæg votlendi eru hefur leitt til ...